Menumbuhkan Sikap Dermawan Pada Peserta Didik Di Lingkungan Sekolah - Arif Rahman Hakim; Nur Ikhsan Kharisma Sitorus (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
Islam teaches its people to have morals or generosity with the aim of having a sense of gratitude for God's blessings, realizing high social sensitivity, and realizing a helpful society. Generosity is a character or character that is rarely found in a person, not everyone has a generous nature. Therefore, this generosity attitude needs to be grown and developed for students in the school environment. So that students will be able to apply it in everyday life. Some ways that schools or educators can do in cultivating this attitude are by giving alms or giving alms. Because, the learning material only explains in a descriptive way the attitude of generosity. However, it is necessary to have actions and intended practices so that these attitudes can grow in students.